STRATEGI PENGATURAN HAK AKSES DAN PROTEKSI DOKUMEN EXCEL UNTUK MENJAGA KEAMANAN DATA BAGI SMK BINUSA - Sutrisno; Okta Irawati; Iis Istiqomah (Abdi Jurnal Publikasi, 2024)
The need to share documents securely becomes crucial, especially on platforms like Microsoft Excel that are widely used for managing sensitive data. The lack of a secure sharing system can lead to the risk of data breaches, such as unauthorized access and document manipulation. This training focuses on strategies for setting access rights and protection in Microsoft Excel to ensure the security of shared data. The main problems found were low pengguna awareness of Excel's security features, weak protection configurations, and threats from external parties due to a lack of access control. The proposed solution optimizes built-in protection features like document encryption and pengguna-based permission settings. This training aims to improve the security of Excel documents through effective management of access rights and a better understanding of available security features. The participants' results showed that using protection features such as passwords and encryption can reduce the risk of unauthorized access. Then implementing pengguna-based permissions increases control over sensitive data and prevents modification by unauthorized parties. In conclusion, a secure Excel document-sharing strategy requires a holistic approach, combining built-in protection features and pengguna education. This training activity for vocational school students provides practical knowledge and guidance for Excel penggunas in maintaining data security.